Experimental Study of Thermal and Mechanical Behaviour of Graphite-Filled UJF Composite - K. Manohar Reddy; D. Harsha Vardhan; Y. Santhosh Kumar Reddy; Gujjala Raghavendra; Ramesh Rudrapati (Advances in Materials Science and Engineering)
The advancement of composites mixed with natural fibers and with fillers has become the most supportable alternative material for engineering applications, especially in industries such as automotive and aerospace. Natural fibers are renewable, cheap, biodegradable, and ecological materials. In the present work, already used woven jute fibers, which are extracted from gunny bags with the same grams per square meter (GSM), were used, and then, woven jute fibers were chemically treated to improve their characteristics. Graphite powder-filled used jute fiber reinforced epoxy composite (UJF) are prepared by using the hand-layup technique. Tests such as tensile, flexure, impact, and thermo-gravimetric analysis (TGA) were conducted. These tests were according to ASTM standards to evaluate the effect of graphite filler content on hybrid epoxy jute composites. The composite material is prepared by changing the content by weight of the filler by 3%, 6%, 9%, and 12%. The experimental results reveal that 6% of the graphite composites showed the maximum tensile strength and modulus. With the increase in the filler content, there is a decrease in the flexural properties. The impact resistance increases slightly up to 6% of the filler content. The study of thermal decomposition showed that the lowest mass loss was found at 9% by weight of the filler content. Morphological analysis performed by FE-SEM showed that the addition of filler content improved the binding of the fiber and matrix up to 6% by weight of the filler content. It should be noted that these hybrid composites are a promising material at low cost for lightweight structural applications.